Microfluidic chambers for monitoring leukocyte trafficking and humanized nano-proresolving medicines interactions - Jones, Caroline N. (National Academy of Sciences, 2012)
Leukocyte trafficking plays a critical role in determining the progress and resolution of inflammation. Although significant progress has been made in understanding the role of leukocyte activation in inflammation, dissecting the interactions between different leukocyte subpopulations during trafficking is hampered by the complexity of in vivo conditions and the lack of detail of current in vitro assays. To measure the effects of the interactions between neutrophils and monocytes migrating in response to various chemoattractants, at single-cell resolution, we developed a microfluidic platform that replicates critical features of focal inflammation sites. We integrated an elastase assay into the focal chemotactic chambers (FCCs) of our device that enabled us to distinguish between phlogistic and nonphlogistic cell recruitment. We found that lipoxin A(4) and resolvin D1, in solution or incorporated into nano–proresolving medicines, reduced neutrophil and monocyte trafficking toward leukotriene B(4). Lipoxin A(4) also reduced the elastase release from homogenous and heterogenous mixtures of neutrophils and monocytes. Surprisingly, the effect of resolvin D1 on heterogenous mixtures was antisynergistic, resulting in a transient spike in elastase activity, which was quickly terminated, and the degraded elastin removed by the leukocytes inside the FCCs. Therefore, the microfluidic assay provides a robust platform for measuring the effect of leukocyte interactions during trafficking and for characterizing the effects of inflammation mediators.